Keragaman Ikan Genus Barbodes di Sungai Nagara Desa Pandak Daun Kecamatan Daha Utara - Siti Zuhroh Zalfaa Muharrimah; Bunda Halang; Mahrudin Mahrudin (Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Species diversity can be defined as the number of species among the total number of individuals of all existing species. The existence of fish, especially fish of the Barbodes genus, is very important for the ecosystem, besides that, fish of the Barbodes genus also function as a source of protein for humans. The purpose of this study was to describe the diversity of fish of the genus Barbodes found in the Nagara River. This research was conducted in the Nagara River, Pandak Daun Village, North Daha District in August-January 2021. There are 2 zones to catch fish, namely settlements and vegetation using a net measuring 10 x 2 m. This research method uses descriptive method with random sampling technique. Diversity was calculated using the Shannon-Wiener diversity index. The results obtained were three types of fish of the genus Barbodes. Namely lampam putih fish (Barbodes gonionotus), lampam merah fish (Barbodes schwanenfeldii), and abang-abang fish (Barbodes altus). The highest diversity with the value H' = 1,04 and the lowest H' = 0,61.